Great potential for biosensor-based technology in diagnosing seed-borne pathogens - Akhtar, Jameel; Kumar, Pardeep; Kiran, Raj; Shekhar, Meena; Sadhna, Sadhna; Dubey, Sunil Chandra (Indian Farming, 2021)
Protein-based immunological and DNA-based polymerase chain reaction methods have been developed for diagnosis of plant pathogens but their utility is limited for certain reasons. Biosensorbased methods are now available as a potential alternative, which are capable to quickly and accurately identify pathogens. Although biosensor-based methods are widely used in different areas such as food-borne microorganisms, Escherichia, Staphylococcus, Salmonella and Listeria, adulteration of foods, estimation of blood sugar and cholesterol, determination of pregnancy in women, etc., but for assessing the health of seeds and plants, it is not in vogue. It is clear from other field’s examples that biosensor-based techniques are able to quickly and accurately identify plant pathogens and can also play a vital role in providing disease-free quality seeds to researchers and farmers. Considering the efforts made in science, increasing expectation level of experimentation and progress, it seems that biosensor-based technologies will prove to be successful in future in the field of plant protection, mainly in disease diagnosis.